Is non-HDL-cholesterol a better predictor of long-term outcome in patients after acute myocardial infarction compared to LDL-cholesterol?: A retrospective study - Wanwarang Wongcharoen (2018)
© 2017 The Author(s). Background: It has recently been shown that non-high density lipoprotein cholesterol (non-HDL-C) may be a better predictor of cardiovascular risk than low density lipoprotein cholesterol (LDL-C). Based on known ethic differences in lipid parameters and cardiovascular risk prediction, we sought to study the predictability of attaining non-HDL-C target and long-term major adverse cardiovascular event (MACE) in Thai patients after acute myocardial infarction (AMI) compared to attaining LDL-C target. Methods: We retrospectively obtained the data of all patients who were admitted at Maharaj Nakorn Chiang Mai hospital due to AMI during 2006-2013. The mean non-HDL-C and LDL-C during long-term follow-up were used to predict MACE at each time point. The patients were classified as target attainment if non-HDL-C <100 mg/dl and/or LDL-C <70 mg/dl. The MACE was defined as combination of all-cause death, nonfatal coronary event and nonfatal stroke. Results: During mean follow-up of 2.6 ± 1.6 years among 868 patients after AMI, 34.4% achieved non-HDL-C target, 23.7% achieved LDL-C target and 21.2% experienced MACEs. LDL-C and non-HDL-C were directly compared in Cox regression model. Compared with non-HDL-C <100 mg/dl, patients with non-HDL-C of >130 mg/dl had higher incidence of MACEs (HR 3.15, 95% CI 1.46-6.80, P = 0.003). Surprisingly, LDL-C >100 mg/dl was associated with reduced risk of MACE as compared to LDL <70 mg/dl (HR 0.42, 95% CI 0.18-0.98, p = 0.046) after direct pairwise comparison with non-HDL-C level. Conclusions: Non-attaining non-HDL-C goal predicted MACE at long-term follow-up after AMI whereas non-attaining LDL-C goal was not associated with the higher risk. Therefore, non-HDL-C may be a more suitable target of dyslipidemia treatment than LDL-C in patients after AMI.